2012
DOI: 10.5923/j.ijbe.20120204.01
|View full text |Cite
|
Sign up to set email alerts
|

RiceWrist Robotic Device for Upper Limb Training: Feasibility Study and Case Report of Two Tetraplegic Persons with Spinal Cord Injury

Abstract: Regaining upper extremity function is the primary concern of persons with tetraplegia caused by spinal cord injury (SCI). Robotic rehabilitation has been inadequately tested and underutilized in rehabilitation of the upper extremity in the SCI population. Given the acceptance of robotic train ing in stroke rehabilitation and SCI gait training, coupled with recent evidence that the spinal cord, like the brain, demonstrates plasticity that can be enhanced by repetitive movement training such as that available wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Second, we used repetitive robotic-assisted training instead of repetitive task practice. Robotic-assisted training with MAHI Exo-II exoskeleton device has produced positive outcomes in other studies from our lab with spinal cord injury patients (Kadivar et al, 2012;Yozbatiran et al, 2012) High intensity repetitive training of elbow flexion/ extension, forearm pronation/ supination, wrist flexion/extension and ulnar/radial deviation was successfully delivered. Within subjects' number of repetition reached up to 1000 on average in onehour.…”
Section: Efficacy Of Combination Therapymentioning
confidence: 86%
“…Second, we used repetitive robotic-assisted training instead of repetitive task practice. Robotic-assisted training with MAHI Exo-II exoskeleton device has produced positive outcomes in other studies from our lab with spinal cord injury patients (Kadivar et al, 2012;Yozbatiran et al, 2012) High intensity repetitive training of elbow flexion/ extension, forearm pronation/ supination, wrist flexion/extension and ulnar/radial deviation was successfully delivered. Within subjects' number of repetition reached up to 1000 on average in onehour.…”
Section: Efficacy Of Combination Therapymentioning
confidence: 86%
“…None of the participants dropped out of the study. Some case reports have described the safety and feasibility of the upper limb robotic training in this population with similar results, high tolerance and no increase in pain or spasticity (Yozbatiran et al, 2012; Sledziewski et al, 2012; Kadivar et al, 2012), using different robotic devices (Armeo, Geo Ro).…”
Section: Discussionmentioning
confidence: 88%
“…It has recently been suggested that when patients present with severely limited capabilities, a longer (>36 weeks) or alternative form of therapy, for example, one combined with stimulation, may be warranted (Kadivar et al, 2012). Lastly, the study lacks adequate follow-up measurements to ensure that the functional gain is retained over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion capture systems for tracking leg motion are widely applied in many fields, such as rehabilitation [1][2][3], competitive training [4], human-computer interaction [5], movie, animation [6], and exoskeleton assist systems [7]. The measurement of joint motion can ensure safe and effectual rehabilitation of leg motion [8]; several systems for leg rehabilitation have been developed that are applied to rehabilitation of spinal cord injury and neurological or orthopedic lesions [9][10][11]. In addition, the capture and analysis of joint motions can improve the competitiveness of some sports.…”
Section: Introductionmentioning
confidence: 99%